Towards an Exhaustive Evaluation of Vision-Language Foundation Models - Salin, Emmanuelle; Ayache, Stéphane; Favre, Benoit (Proceedings - 2023 IEEE/CVF International Conference on Computer Vision Workshops, ICCVW 2023, 2023)
Vision-language foundation models have had considerable increase in performances in the last few years. However, there is still a lack comprehensive evaluation methods able to clearly explain their performances. We argue that a more systematic approach to foundation model evaluation would be beneficial to their use in real-world applications. In particular, we think that those models should be evaluated on a broad range of precise capabilities, in order to bring awareness to the width of their scope and their potential weaknesses. To that end, we propose a methodology to build a taxonomy of multimodal capabilities for vision-language foundation models. The proposed taxonomy is intended as a first step towards an exhaustive evaluation of vision-language foundation models.
Created from Fastlane, Scopus look-up
Keywords: Foundation models; Language; Transformers; Vision